2003
DOI: 10.1590/s0104-14282003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Polietileno: principais tipos, propriedades e aplicações

Abstract: Resumo: A estrutura de cada polímero tem influência direta sobre a sua densidade e suas propriedades mecâ-nicas. Ramificações longas, como as presentes no polietileno de baixa densidade, por exemplo, aumentam a resistência ao impacto, diminuem a densidade e facilitam o processamento, enquanto que as ramificações curtas, presentes no polietileno linear de baixa densidade, aumentam a cristalinidade e a resistência à tração em relação ao polietileno de baixa densidade (obtido via radicais livres). As principais a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0
55

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 22 publications
7
43
0
55
Order By: Relevance
“…Similar results have been reported in literature and they have been attributed to the immiscibility of LDPE/PHB blends and the weak interfacial adhesion between the two polymers [6] . However, it may be emphasized that the tensile strength value of the 70/30 LDPE/PHB blend (9.1 MPa) is quite similar to the values presented by some grades of LDPE [22] .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results have been reported in literature and they have been attributed to the immiscibility of LDPE/PHB blends and the weak interfacial adhesion between the two polymers [6] . However, it may be emphasized that the tensile strength value of the 70/30 LDPE/PHB blend (9.1 MPa) is quite similar to the values presented by some grades of LDPE [22] .…”
Section: Resultssupporting
confidence: 73%
“…However, the tensile values of these blends lie in the range of the values presented by some commercial grades of LDPE [22] .…”
Section: Resultsmentioning
confidence: 66%
“…[25][26][27][28][29][30][31][32][33] Os valores de resistência à tração encontrados no presente estudo são inferiores aos relatados para filmes sintéticos de polietileno de baixa densidade (PEBD), que variam de 6,9 a 16 MPa. 34 …”
Section: Resultsunclassified
“…The polyethylene (PE) is a flexible semi-crystalline polymer whose properties are influenced by the relative amount of amorphous and crystalline phases. One of the most common polymers is the low-density polyethylene (LDPE), which has a crystallinity about 50-60%, a melting temperature in the range of 110-115 °C and branched chains that determines the degree of crystallinity and the transition temperatures [13] . The results from a previous study on the degradation of this polymer in different conditions showed positive effects, especially when the photo and biodegradation experiments have been carried out in combination [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%